Improving Students’ Listening Skill on Numbers through Songs at The First Semester in English Language Study Program San Pedro University - Sene, Chamelya; Lodo, Rozita Y.; Tefa, Antonia; Mola, Mansuetus (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Four essential skills must be mastered in order to study the English language. They are speaking, listening, writing, and reading. Proficiency in the English language requires mastery of the fourth such ability. One of the abilities that must be understood when learning English is listening. Using songs is one of the numerous strategies to enhance listening abilities. The purpose of this research is to ascertain whether employing English songs throughout the first semester of San Pedro University's English language study program improves students' listening abilities. Action research in the classroom was used in this study. The 15 students served as the research subjects. The researcher implemented teaching and assessments to gather data. The average score was 71.33 in the first cycle, and 46.66% of students achieved the standard score, as indicated by the data. In contrast, 86.66% of students passed score in the second cycle, with an average score of 78.66. However, observations show that during listening exercises, some students are still unable to hear the music being played clearly. In the second cycle, students demonstrated an enhancement in their listening skills through the utilization of English songs. San Pedro University has seen a rise in the use of song lyrics for listening according to the research’s findings.